Anxiety in families of individuals with neurodevelopmental conditions in the early months of the COVID-19 pandemic in Switzerland - Di Poi, Giona; Dukes, Daniel; Meuleman, Ben; Banta Lavenex, Pamela; Lavenex, Pierre; Papon, Anouk; Tran, Michel; Stallmann, Lina; Treichel, Noémie; Samson, Andrea C. (Frontiers in Education, 2023)
In the spring of 2020, the COVID-19 pandemic generated a health, social, political, and economic crisis that dramatically reduced the institutional support for families of individuals with neurodevelopmental conditions (NDCs). To understand how these families may have experienced and coped with the pandemic, we created an online questionnaire that reached more than 10,000 families in 78 countries. The current manuscript - framed within the International Classification of Functioning, Disability and Health (ICF-10) model - investigates the impact of specific health conditions and personal or environmental factors on the anxiety of families living in Switzerland during the early months of the pandemic. To assess how differences in anxiety over time were predicted by specific health conditions or personal and environmental factors, two separate multilevel analyses were conducted for parents and their children with NDCs (N = 256). First, results showed that only parents reported an increase in anxiety when the pandemic started. Second, concerns related to loss of institutional support and financial and economic problems were the most anxiety-provoking factors for parents, whereas parents reported that the most anxiety-provoking factor for children was their concern about becoming bored. Many parents may have struggled with economic problems and managed multiple extra roles and tasks in their daily lives because institutional support was no longer available. As reported by their parents, although individuals with NDCs did not show an increase in anxiety, they may have struggled with boredom. This result may represent the inability to engage in satisfactory activities in daily life associated with a partial unawareness of the pandemic and the respective protective measures. Further research should more thoroughly investigate the potential effects of the individual’s primary condition, presence and severity of intellectual disability and awareness of the pandemic on the anxiety of individuals with NDCs. Ultimately, we present a series of reflections and practical suggestions that could help guide policymakers in potential future periods of crisis, social estrangement, and distance learning.